Evaluative Language as Portrayed in The Texas Chainsaw Massacre Movie Review by Roger Ebert: An Appraisal Analysis - Eva Crystalia; Sunardi Sunardi (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2018)
Abstract. This paper analyzes the appraisal system of The Texas Chainsaw Massacre  movie review by Roger Ebert. This study aims at analyzing the evaluation given by the reviewer toward the movie. The data of this research are all clauses containing appraising items toward the movie. The data were analyzed by using descriptive qualitative method and analytical frameworks suggested by Martin and White (2005) and Martin and Rose (2003) on appraisal system in systemic functional linguistics (SFL). Based on the analysis, the researcher found that the kind of appraising item mostly used by the reviewer is attitudinal lexis (35%) and the least used items are relational process (1%) and modality clause (1%). The attitude is mostly appreciation (59%), followed by affect (26%) and judgment (15%). For the engagement, the evaluations are classified as monogloss (99%) and heterogloss (1%). For the graduation, the evaluations are classified as down-scaled (76%) and up-scaled (24%). It can be concluded that the reviewer tends to use attitudinal lexis in his evaluation. The evaluations are mostly sourced from the reviewer himself. The reviewer tends to evaluate things more than people, and his evaluations are mostly to be negative toward the movie.Keywords: appraisal system; movie review; evaluation languageAbstrak. Paper ini membahas tentang sistem appraisal pada teks review yang ditulis oleh Roger Ebert dari film The Texas Chainsaw Massacre. Data penelitian mencakup seluruh klausa dalam teks review yang dikaji yang memuat kata-kata appraisal terhadap film yang ditelaah. Data dianalisis secara deskriptif kualitatif dengan menggunakan kerangka analisis yang dikemukakan oleh Martin, Rose, dan White tentang sistem appraisal dalam linguistik sistemik fungsional (SFL). Hasil analisis menyatakan bahwa lebih banyak menggunakan attitudinal lexis (35%), dan sedikit menggunakan proses relasional (1%) dan klausa modalitas (1%). Jenis-jenis attitude yang digunakan adalah apresiasi (59%), afek (26%), dan judgement (15%). Dalam engagement, jenis evaluasi yang digunakan meliputi monogloss (99%) dan heterogloss (1%). Dalam graduation, evaluasi dilakukan secara down-scaled (76%) dan up-scaled (24%). Sumber evaluasi sebagian besar berasal dari penelaah (reviewer) sendiri. Sebagian besar materi yang dievaluasi adalah benda daripada orang, dan penilaian terhadap film ini cenderung negatif.        Kata kunci: sistem appraisal; teks telaah film; bahasa evaluatif